Antibacterial shower gel from clitoria ternatea linn leaves extract / Nuraina Aqilah Ismail - Ismail, Nuraina Aqilah (2022)
Clitoria ternatea Linn, also known as butterfly pea plant by natives, is a major plant used in Ayurveda and traditional medicine all around the world. It is also used for a variety of purposes in the food and cosmetic industries. In this study, the leaves part of Clitoria ternatea Linn was extracted by Soxhlet extraction method and ethanol was used as the solvent. After extraction, the percentage yield of the ethanolic leaves extract of Clitoria ternatea L. attained was 5.57%. This study aims to determine the phytochemical constituents present in the crude extract of Clitoria ternatea L. leaves by qualitative preliminary phytochemical screening tests. Major chemical constituents identified in the leaves extract are alkaloids, tannins, glycosides, saponins, phenols and coumarins. The objective of this study is also to evaluate the antibacterial activity of Clitoria ternatea Linn ethanolic leaves extract by antibacterial agar disc diffusion assay against two distinct bacterial strains which are Gram-positive and Gram-negative bacteria. The antibacterial activity of leaves extract is the highest at concentration of 30 ppm as it showed the highest mean of inhibition zone for Bacillus licheniformis and Escherichia coli which are 16.33 mm and 14.67 mm respectively compared to 20 ppm and 10 ppm. This study also aims to produce an antibacterial shower gel from 30 ppm of Clitoria ternatea L. leaves extract by using a liquid soap base. The mean of inhibition zone for shower gel against B. licheniformis is higher than E. coli which is 11.33 mm and 10.33 mm respectively. However, shower gel showed devoid antibacterial activity at 30 ppm since its mean inhibition zone for both bacteria is less than 12 mm and categorized as no inhibitory effects due to low concentration of leaves extract. Therefore, from this study, it can be concluded that the leaves extract of Clitoria ternatea Linn contains many active phytoconstituents which contributing to antibacterial activity against Gram-positive and Gram-negative bacterial strains.